2018
DOI: 10.2196/10361
|View full text |Cite
|
Sign up to set email alerts
|

Combining Technology and Research to Prevent Scald Injuries (the Cool Runnings Intervention): Randomized Controlled Trial

Abstract: BackgroundNew technologies, internet accessibility, social media, and increased smartphone ownership provide new opportunities for health researchers to communicate and engage target audiences. An innovative burn prevention intervention was developed using these channels.ObjectiveThe aim of this study was to evaluate the efficacy of Cool Runnings, an app-based intervention to increase knowledge of childhood burn risk (specifically hot beverage scalds) and correct burn first aid among mothers of young children.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 34 publications
1
35
0
1
Order By: Relevance
“…Attrition in our study was quite similar to that reported at 6-month follow up for an educational app on car seat use [ 25 ] (34.3%, 387/1129), but was significantly lower than the rate of 51% (254/498) reported in an app-based study of scald burn prevention [ 22 ]. A wide range of factors likely explain participant attrition from engagement in an app-based intervention, including design of the app, assessment measures for participant compliance, individual characteristics of participants, and cultural differences across countries.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Attrition in our study was quite similar to that reported at 6-month follow up for an educational app on car seat use [ 25 ] (34.3%, 387/1129), but was significantly lower than the rate of 51% (254/498) reported in an app-based study of scald burn prevention [ 22 ]. A wide range of factors likely explain participant attrition from engagement in an app-based intervention, including design of the app, assessment measures for participant compliance, individual characteristics of participants, and cultural differences across countries.…”
Section: Discussionsupporting
confidence: 82%
“…We hypothesized that a more active and attractive type of intervention would result in greater engagement and thus a lower attrition rate in the intervention arm compared with the control arm. Replicating Burgess et al [ 22 ] and others, we also hypothesized that greater education might be related to higher retention in the intervention study. We used data collected from a cluster randomized controlled trial (RCT) examining an app intervention to prevent unintentional child injury in China to test our hypotheses.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…To date, however, only a few mobile phone app interventions are available to assist parents in preventing unintentional child injuries, and most are not based in theory or are insufficiently tested in rigorous randomized trials [11]. Tests of these interventions were conducted in HICs [12-15] and generally involved assessments of knowledge, perception, and behavioral outcomes with relatively small sample sizes [12,14] (eg, the sample sizes in studies by Gielen et al [12] and Burgess et al [14] were 498 and 742, respectively). None have used actual injury events as the primary outcome indicator [12-15].…”
Section: Introductionmentioning
confidence: 99%